Association of Synergistetes and Cyclodipeptides with Periodontitis. (October 2015) - Marchesan, J.T.; Morelli, T.; Moss, K.; Barros, S.P.; Ward, M.; Jenkins, W.; Aspiras, M.B.; Offenbacher, S.
The purpose of this study was to evaluate the microbial community (MC) composition as it relates to salivary metabolites and periodontal clinical parameters in a 21-d biofilm-overgrowth model. Subjects ( N = 168) were enrolled equally into 5 categories of periodontal status per the biofilm-gingival interface classification. Microbial species within subgingival plaque samples were identified by human microbiome identification microarray. Whole saliva was analyzed by liquid chromatography–mass spectrometry and gas chromatography–mass spectrometry for metabolite identification. Phylum was grouped into MCs according to principal component analysis. Generalized linear and regression models were used to examine the association among MC, species, periodontal clinical parameters, and salivary metabolome. Multiple comparisons were adjusted with the false discovery rate. The study population was distributed into 8 distinct MC profiles, designated MC-1 to MC-8. MC-2 explained 14% of the variance and was dominated by Synergistetes and Spirochaetes. It was the only community structure significantly associated with high probing depth ( P = 0.02) and high bleeding on probing ( P = 0.008). MC-2 was correlated with traditional periodontal pathogens and several newly identified putative periodontal pathogens: Fretibacterium fastidiosum, Fretibacterium sp. OT360/OT362, Filifactor alocis, Treponema lecithinolyticum, Eubacterium saphenum, Desulfobulbus sp. / OT041, and Mogibacterium timidum. Synergistetes phylum was strongly associated with 2 novel metabolites—cyclo (-leu-pro) and cyclo (-phe-pro)—at 21 d of biofilm overgrowth ( P = 0.02). In subjects with severe periodontitis (P2 and P3), cyclo (-leu-pro) and cyclo (-phe-pro) were significantly associated with increased changes in probing depth at 21 d of biofilm overgrowth ( P ≤ 0.05). The analysis identified a MC dominated by Synergistetes, with classic and putative newly identified pathogens/pathobionts associated with clinical disease. The metabolomic discovery of 2 novel cyclodipeptides that have been reported to serve as quorum-sensing and/or bacteriocidal/bacteriostatic molecules, in association with Synergistetes, suggests a potential role in periodontal biofilm dysbiosis and periodontal disease that warrants further investigation.